Conversational Implicature in Steve’s Talented Kids: An Analysis of the “Extraordinary Kids Edition” Episode (Sastra Inggris UNPAM, 2026)
This study aims to identify how conversational implicature is used in selected videos from Steve’s TV Show, specifically the episode titled “Extraordinary Kids Edition” featuring “Steve’s Talented Kids.” The study employed a descriptive qualitative approach and applied Grice’s (1975) theory of conversational implicature as the analytical framework. Based on the analysis, seven instances of conversational implicature were identified. The findings indicate that violations of the maxim of quality occurred more frequently than violations of other maxims, making it the most dominant source of conversational implicature in the data. Overall, the analysis revealed violations of several Gricean maxims, including quantity, quality, relevance, and manner. One instance involved a violation of the maxim of quantity, reflecting an imbalance in the amount of information provided. Three instances violated the maxim of quality, suggesting the use of inaccurate or exaggerated information. One instance violated the maxim of relevance, where the response was not directly related to the conversational context. Finally, two instances violated the maxim of manner, indicating unclear or overly complex expressions. These violations of conversational maxims contributed to the emergence of implicature through various pragmatic strategies, such as incomplete information, inaccurate statements, irrelevant responses, and ambiguous or indirect modes of expression..